The profile and manifestation of moral decay in South African urban community - Sekhaulelo, Motshine A. (HTS teologiese studies, 2021)
South Africa in which we are living is characterised by unparalleled social and political change and apparently enormous differences of option. However, there is one aspect of our society that most of us would probably agree about and that is the decline of morality in our cities. Apart from the economic and political crisis, and the erosion of the core competence to actually get things done in the municipalities, South Africa is an ailing society with disturbing pathologies in terms of indiscipline, violence, rape, assault, fraud and a failure to accept personal accountability for the high levels of crime, corruption, xenophobic attacks, gender-based violence and disintegration of families. The main aim of this study is to outline the profile of moral decay in the South African urban community and to define the calling of the Church towards moral regeneration. The conclusion arrived at is that there are definite signs of moral degeneration over a wide sphere of human endeavour in South African urban community, and that the church has a particular role to play as a driving agent for moral renewal.Contribution: Whilst there are many postive things brought by urbanisation in our cities, however, moral decay in our South African cities is one of the biggest threats to South Africa’s hard earned, freedom and democracy and merits closer attention. This study in ethics joins the voices of those people who are propagating moral regeneration in our times.